Study of nitrogen-containing compounds for quantum dot photonics - Yoon, Soon Fatt. (2012)
Following the first successful demonstration of the transistor in 1947, a revolution in technology took place, which profoundly shaped our society. The transition from the industrial age to the information age was entirely driven by progress in science and technology. Similarly, several emerging technologies are expected to shape our near future as greatly as the silicon technology did. Among these modern research fields we find nanotechnology: the science on the scale of atoms and molecules, so small that the peculiar effects of quantum mechanics can be observed and utilized.